Measuring impacts - The experience of the EIB-GDN programme - European Investment Bank (2022)
Measuring, understanding and communicating the EIB's development impact is a key strategic priority for the European Investment Bank (EIB). In partnership with the Global Development Network the EIB started the Programme in Applied Development Finance in 2017, to deepen understanding of results and impact of operations under the Impact Financing Envelope (IFE) for Africa Caribbean and the Pacific (ACP), as well as enhancing capacity for impact assessment in ACP countries and within EIB. The research was carried out in three twelve-month cycles, by talented researchers from ACP countries. Each spent a year on a "deep dive" study of an IFE project, trained, guided and mentored by GDN, the EIB and expert advisors (EAs). The programme used academic research techniques to study the development impact of ongoing private-sector investments, built and used capacity for evaluative research in developing countries, and boosted accountability and development effectiveness. This book discusses lessons learnt and opportunities for future work of this three-year partnership.